ANALISIS PENGAMBILAN KEPUTUSAN NASABAH MEMILIH PRODUK-PRODUK PEMBIAYAAN DI KOPERASI SYARIAH PEGAWAI RSUD Dr. ACHMAD MOCHTAR BUKITTINGGI - Halisa Nugrah Lubis; Novera Martilova (Jurnal Ekonomi dan Bisnis, 2025)
The Sharia Cooperative of Employees of Dr. Achmad Mochtar Hospital, Bukittinggi, has seen a fluctuation in the number of clients of murabahah and jasat finance goods, which is what drove this research. Finding out how customers at the Sharia Cooperative of Employees of Dr. Achmad Mochtar Hospital in Bukittinggi makes decisions about financing products as the main goal of this study. We also want to know what problems customers face and how we can solve them. The data for this study came straight from the source, as it is a field study. A qualitative descriptive research approach is used in this study. Consumers of financial services oflered by the Sharia Cooperative of Stafl at Bukittinggi's Dr. Achmad Mochtar Hospital is the primary data set for this research. Observation, interviews, and documentation are the methods used to gather data in this study. Customer decision-making in choosing financing products at the sharia cooperative incorporates diflerent elements, both financial and connected to sharia principles, according to the author's research. These factors include aligned principles, suggestions, and experiences; kinds of contracts and financing arrangements; the presence of narrow margins; and terms and conditions that must be in conformity with the fatwa and requirements of the DSN-MUI. Sharia Cooperative of Employees of Dr. Achmad Mochtar Hospital Bukittinggi continues to face customer-side barriers in the finance analysis. Due to a lack of knowledge of sharia principles, the client has difficulties. An educational program outlining the concepts and functioning of sharia could be provided by the Sharia Cooperative of Employees of Dr. Achmad Mochtar Hospital Bukittinggi as a solution. The Sharia Cooperative of Employees of Dr. Achmad Mochtar Hospital, Bukittinggi, has seen a fluctuation in the number of clients of murabahah and jasat finance goods, which is what drove this research. Finding out how customers at the Sharia Cooperative of Employees of Dr. Achmad Mochtar Hospital in Bukittinggi makes decisions about financing products as the main goal of this study. We also want to know what problems customers face and how we can solve them. The data for this study came straight from the source, as it is a field study. A qualitative descriptive research approach is used in this study. Consumers of financial services oflered by the Sharia Cooperative of Stafl at Bukittinggi's Dr. Achmad Mochtar Hospital is the primary data set for this research. Observation, interviews, and documentation are the methods used to gather data in this study. Customer decision-making in choosing financing products at the sharia cooperative incorporates diflerent elements, both financial and connected to sharia principles, according to the author's research. These factors include aligned principles, suggestions, and experiences; kinds of contracts and financing arrangements; the presence of narrow margins; and terms and conditions that must be in conformity with the fatwa and requirements of the DSN-MUI. Sharia Cooperative of Employees of Dr. Achmad Mochtar Hospital Bukittinggi continues to face customer-side barriers in the finance analysis. Due to a lack of knowledge of sharia principles, the client has difficulties. An educational program outlining the concepts and functioning of sharia could be provided by the Sharia Cooperative of Employees of Dr. Achmad Mochtar Hospital Bukittinggi as a solution.